Effects Of Climate Change In The Distribution Of Oyamel Forest - Araiza-Olivares, Gabriel Alexis (Revista Geográfica de América Central., 2020)
Oyamel (Abies religiosa) is an endemic species of Mexico; the masses that form are distributed in isolated patches, in the mountainous regions of the center of the country. For its development requires specific environmental conditions of cool temperatures and high humidity. Oyamel forests are a great reservoir of biodiversity since they house hundreds of species of flora and fauna. Likewise, they fulfill the function of important carbon sinks and water collectors, besides having an important economic potential since they provide raw materials for several industries, among other environmental services. Although climate change is not an unprecedented phenomenon, the speed observed today suggests that its origin is not natural but anthropic. This paper analyzed the long-term effects that climate change, according to the REA model, would have on the extension and distribution of oyamel forests in the Transversal Volcanic System. The results were divided into five categories (Very adequate, Adequate, Moderately adequate, Unsuitable and Unsuitable), depending on the ombrothermic conditions of the different radiative forcings of the model showed a significant decrease in the territorial extent occupied by this ecosystem, while observing an altitudinal rise in its distribution.